3 THE REVISED STATUTES, CODE AND GENERAL LAWS OF THE STATE OF NEW YORK 3330, § 2 (Clarence F. Birdseye ed., 1890) - (:unkn) unknown (General Publisher, 1890)
Prohibited carrying with intent to use any slungshot, billy, sand-club, metal knuckles, dagger, dirk, dangerous knife. Violators guilty of a felony. Minors guilty of a misdemeanor.
--
Keywords: CARRY - NON-GUN ARMS